Pelatihan Penulisan Artikel Ilmiah Bagi Mahasiswa PPKn Universitas PGRI Yogyakarta - T Heru Nurgiansah (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The task of a student is not only to follow regular learning such as face-to-face lectures, doing individual and group assignments, taking the Final Semester Examinations, KKN, PPL, and Thesis. However, students are now required to be able to write a scientific paper. Moreover, lectures in the Pancasila and Citizenship Education Study Program use journal-based lectures, so every lecture material must be sourced from national and international journals. This service aims to train students to write scientific articles which can later be published in accredited National Journals. The training lasts for 3 days. This training method uses a variety of lectures and direct practice. As for the result of this dedication, the students succeeded in making one scientific paper each that was ready to be published.